FENOMENA KOMUNIKASI KOMUNITAS BATU AKIK DI KOTA PEKANBARU (STUDI FENOMENOLOGI PADA ANGGOTA KOMUNITAS ASOSIASI PERMATA RIAU (APR) ) - NI Putu G Widhi A; Welly Wirman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Discussing about the lifestyles means also talking about the trend with the times. At the end - the end of the trend of wearing jewelery decorated precious stones (agate) are rampant among the wider community among parents and young people. Due to the discovery of different kinds of stones, colors and things that contains the value in terms of both economic and mystical in the rock so that the precious stone into one of the phenomena in Indonesia and because of these things comes the interest in the same interests, forming associations or community in this community Permata Riau Association (APR). This study aims to determine the motive of the community members in collecting and joined APR and also to know the meaning and communication experience gained by members of the APR. This study uses qualitative research methods with the presentation of descriptive analysis. Data collection techniques used were observation, interviews and documentation. In reaching the validity of the data in this study, researchers used the extension of participation and triangulation. Subjects were community members APR whereas research objects and motifs communication experience acquired in the community APR. The results of this study indicate that the reason why they join into the community APR for their motives past and future as well agate interpreted as a medium of self-expression as well media communication among lovers of rock and also get communication experience pleasant and unpleasant during Circles APR.Keywords: phenomena, communication, community, agate